Geochemistry of mafic–ultramafic magmatism in the Western Ghats belt (Kudremukh greenstone belt), western Dharwar Craton, India: implications for mantle sources and geodynamic setting. Issue 12 (10th September 2017) - B, Chandan-Kumar; Ugarkar, A. G.
ABSTRACT: Western Ghats Belt of western Dharwar Craton is dominated by metavolcanic rocks (komatiites, high-magnesium basalts (HMBs), basalts, boninites) with occasional metagabbros. This rock-suite has undergone post-magmatic alteration processes corresponding to greenschist- to lower-amphibolite facies conditions. Komatiites are Al-depleted, characterized by lower Al2 O3 /TiO2 and high CaO/Al2 O3 . Their trace element distribution patterns suggest most of the primary geochemical compositions are preserved with minor influence of post-magmatic alteration processes and negligible crustal contamination. Chemical characteristics of Al-depleted komatiites imply their derivation from deeper upper mantle with/without garnet involvement. HMBs and basalts are differentiated based on their magnesium content. Basalts and occasionally associated gabbroic sills have similar geochemical characteristics. HMB are characterized by light rare earth element (LREE) enrichment, with significant Nb–Ta and Zr negative anomalies. Basalts and associated gabbros display tholeiitic affinity, with LREE-enriched to slightly fractionated heavy rare earth element (HREE) patterns. Boninites are distinctive in conjunction of low abundances of incompatible elements with respect to the studied komatiites. Chondrite-normalized REE patterns of boninites show relative enrichment in LREE and HREE with respect to MREE. Prominent island arc signatures are evident in HMB, basalts, boninites, and gabbros in terms of their Nb–Ta and Zr–Hf negative anomalies, LREE enrichment and HFSE depletion. It is suggested that these HMB–basalts (associated gabbros)–boninites are the products of arc magmatism. Their REE chemistry attests to a gradual transition in melting depth varying between spinel and garnet stability field in an arc regime. The close spatial association but contrasting elemental characteristics of komatiites and HMB–basalts–boninites can be explained by a plume-arc model, in which the ~3.0 Ga komatiites are considered to be the products of plume volcanism in an oceanic setting, while the HMB, basalts, boninites, and associated gabbros were emplaced in a continental margin setting around 2.8–2.7 Ga.